The Figure of The Child in James Reaney's Poetry - Ameer , Hassan Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to shed light on Canadian poetry in general and in more specific the poetry of James Reaney as an emblem figure of Canadian literature. It focuses on the concept of image and how the poet employs the image of child to carry out his literary and moral messages to his readers. This study is innovative and valuable since it tries to explore a selected number of Reaney's poetry in order to explore his vision of his society as well as to the way he uses the imagistic picture of child to address his adult readers to deliver his messages.